Virtual PET Scanner – From Simulation in GATE to a Final Multiring Albira PET/SPECT/CT Camera - Balcerzyk, M.; Caballero, L.; Correcher, C.; Gonzalez, A.; Vazquez, C.; Rubio, J.L.; Kontaxakis, G.; Pozo, M.A.; Benlloch, J.M. (IntechOpen, 2012)
None